PENGARUH ESG, KUALITAS LABA, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Dwi Septiani; Dita Kurnia Sari; Niser (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG), earnings quality, and firm size on firm value in companies listed on the Indonesia Stock Exchange (IDX). This research employs a quantitative approach using panel data regression analysis based on secondary data from financial and sustainability reports. Model selection is conducted through the Chow test, Hausman test, and Lagrange Multiplier test using EViews 12. The results show that ESG, earnings quality, and firm size simultaneously affect firm value. Partially, ESG has no significant effect on firm value, while earnings quality and firm size have a significant effect. These findings indicate that financial factors remain the primary consideration for investors in the Indonesian capital market.